2017
DOI: 10.1007/s11104-017-3353-3
|View full text |Cite
|
Sign up to set email alerts
|

Leaf habit of tree species does not strongly predict leaf litter decomposition but alters climate-decomposition relationships

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer International Publishing AG. This e-offprint is for personal use only and shall not be selfarchived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later and provided ackn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 79 publications
(180 reference statements)
0
7
0
Order By: Relevance
“…In what concerns sempervirent broadleaved trees, its rate of SOC stock change is mostly affected by plantation age rather than climatic conditions (Table 4). This is because (1) the litter production of sempervirent broadleaved trees, which is a major source of SOC input, increases substantially with stand ages; (2) sempervirent broadleaved trees are usually distributed in subtropical or tropical regions, where there is little variations in temperature and precipitation (Ge et al 2017).…”
Section: Management Implicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…In what concerns sempervirent broadleaved trees, its rate of SOC stock change is mostly affected by plantation age rather than climatic conditions (Table 4). This is because (1) the litter production of sempervirent broadleaved trees, which is a major source of SOC input, increases substantially with stand ages; (2) sempervirent broadleaved trees are usually distributed in subtropical or tropical regions, where there is little variations in temperature and precipitation (Ge et al 2017).…”
Section: Management Implicationsmentioning
confidence: 99%
“…For example, a negative effect of precipitation was detected by Zhang et al (2010), whereas a positive effect was documented by Shi et al (2013). This inconsistency may be due to the interaction effects between leaf habit (deciduous broadleaved trees versus sempervirent broadleaved trees) and climate on the decomposition of leaf litter (Ge et al 2017). Climate sensitivities of leaf litter decomposition vary across tree types.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The type of factors that could explain the spatial variation of N 2 O flux differed among different scales. For example, studies under global or regional scale showed that the interaction of climatic, biotic, and edaphic factors accounted for significant portions of the variations in a variable [36][37][38]. Based on this, we speculated that such a phenomenon might be caused by the comprehensive and complicated influence of climatic or biotic factors on N 2 O flux, in a larger scale, which would potentially obscure the true role of edaphic effects.…”
Section: The Explanatory Power Of Five Edaphic Factors For N 2 O Fluxmentioning
confidence: 91%